2020
DOI: 10.1177/0003319720909056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Elevated Pulmonary Artery Systolic Pressure on Short-Term Prognosis in Patients With Acute Myocardial Infarction

Abstract: Pulmonary artery systolic pressure (PASP) may increase because of cardiac alterations that result in increased filling pressures after acute myocardial infarction (AMI). We hypothesized that PASP might be a useful maker to predict the risk of cardiac death after AMI. We carried out a retrospective study from 2013 to 2017 involving 5401 patients with AMI. Patients were grouped according to their admission PASP result, and the primary end point was cardiac death in 6 months after AMI. Pulmonary artery systolic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…We read with interest the article entitled "Effect of Elevated Pulmonary Artery Systolic Pressure on Short-Term Prognosis in Patients With Acute Myocardial Infarction" by Fan et al 1 The authors 1 concluded that pulmonary artery systolic pressure (PASP) was an independent risk factor for 6-month cardiac death in patients with acute myocardial infarction (AMI). Pulmonary artery systolic pressure was associated with age, Killip classification, and decreased ejection fraction.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…We read with interest the article entitled "Effect of Elevated Pulmonary Artery Systolic Pressure on Short-Term Prognosis in Patients With Acute Myocardial Infarction" by Fan et al 1 The authors 1 concluded that pulmonary artery systolic pressure (PASP) was an independent risk factor for 6-month cardiac death in patients with acute myocardial infarction (AMI). Pulmonary artery systolic pressure was associated with age, Killip classification, and decreased ejection fraction.…”
mentioning
confidence: 99%
“…They 1 included 5401 patients (age range of 21-96 years), consisting of acute ST-segment elevation myocardial infarction (n ¼ 2539) and acute non-ST-segment elevation myocardial infarction (n ¼ 2862). Transthoracic echocardiographic measurement of PASP was measured within 48 hours after admission.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We appreciate the comments of Pamukcu and Acikel 1 about our paper entitled “Effect of Elevated Pulmonary Artery Systolic Pressure on Short-Term Prognosis in Patients with Acute Myocardial Infarction.” 2 We would like to state that this was a retrospective study, which mainly reflected the independent effect of pulmonary artery systolic pressure (PASP) on short-term death, without further subgroup analysis, such as the analysis of association between PASP and acute myocardial infarction (AMI) site, revascularization time, or diuretics.…”
mentioning
confidence: 99%